Options for Controlling Type 2 Diabetes during Ramadan - Almalki, Mussa H.; Alshahrani, Fahad (Frontiers in Endocrinology, 2016)
Muslim population worldwide is about 1.5 billion. Based on a global diabetes prevalence of 4.6%, it is estimated that there are about 50 million Muslim with diabetes worldwide observe fasting during the month of Ramadan each year. Ramadan, one of the five pillars of Islam and the ninth month in the Islamic calendar, involves fasting from sunrise to sunset. During the fast, Muslims are required to refrain from eating food, drinking, use of medications, as well as from smoking from dawn to after sunset with no restrictions on food or fluid intake between sunset and dawn. Islam exempts people from duty of fasting if they sick or fasting may affect their health as fasting for patients with diabetes carries a risk of an assortment of complications including hypoglycaemia and post-prandial hyperglycemia as well as metabolic complications associated with dehydration. Nevertheless, a large number of people with diabetes who still choose to fast during Ramadan despite of the advice of their doctor and the permission of religious authorities thereby creating a medical challenge for themselves and their healthcare provider. It is therefore, important for patients with diabetes who wish to fast during Ramadan to make the necessary preparations in order to undertake the fast as safely as possible. This review presents a guide to the care of diabetic patients during Ramadan to help them to fast safely if they wish to do so.